ANALISIS KUALITAS PELAYANAN KHITAN ANAK PEREMPUAN DI KLINIK DR.WAWAN - Andra Fristasya; Agus Salim (LPPM Universitas Awal Bros, 2022)
Satisfaction there is very related to the expected services and the reality of the services that have been provided by The Khitan Anak Perempuan Clinic dr. Wawan. Satisfaction will be fulfilled if the services provided are felt to have been in accordance with the expectations of patients this study aims to find out the picture of patient satisfaction with the services of Khitan Anak Perempuan Clinic dr. Wawan. This type of research is quantitative using questionnaires. The study respondents were patients who received services at Khitan Ank Perempuan Clinic dr. Wawan research results get a total of 50 respondents. The results of the analysis fall into the category of very good or very satisfied. The conclusion of this study is the level of patient satisfaction with the services of The Khitan Anak Perempuan Clinic dr. Wawan.